Design of a Digital Height and Weight Measuring Instrument Using Ultrasonic Sensors and Weight Sensors Based on Arduino Uno: Rancang Bangun Alat Ukur Tinggi Badan dan Berat Badan Digital Menggunakan Sensor Ultrasonik dan Sensor Berat Berbasis Arduino Uno - Sandi, Aji (Journal of Vocational Education and Information Technology (JVEIT), 2023)
Digital height and weight measuring devices are important tools in monitoring individual health. In this study, we propose the design of a height and weight measuring instrument that uses an ultrasonic sensor and a weight sensor based on Arduino Uno. Ultrasonic sensors are used to measure body height by sending ultrasonic waves towards the user and then detecting the time required for the waves to return to the sensor after being reflected by the surface above the user's head. Using simple trigonometry principles, the user's height can be calculated accurately. Meanwhile, a weight sensor is used to measure body weight. The user's weight is placed on a platform equipped with a weight sensor. The data generated by the sensor is then processed by Arduino Uno to calculate body weight with precision. The height and weight measurement data is displayed digitally on the LCD screen installed on the tool. In addition, this tool is also equipped with the ability to save measurement data so that users can track changes in their height and weight over time. Testing is carried out to verify the accuracy and reliability of the tool. Test results show that this tool is able to measure height and weight with a high level of accuracy. Thus, this tool can be an effective and efficient solution for monitoring personal health.